-4-6t=6t+32

Simple and best practice solution for -4-6t=6t+32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-6t=6t+32 equation:


t in (-oo:+oo)

-(6*t)-4 = 6*t+32 // - 6*t+32

-(6*t)-(6*t)-32-4 = 0

-6*t-6*t-32-4 = 0

-12*t-36 = 0 // + 36

-12*t = 36 // : -12

t = 36/(-12)

t = -3

t = -3

See similar equations:

| -5+x=6x-55 | | 6n+10=5n+15 | | 2b+1=-5b+71 | | 7d-3=3d-47 | | 5b-10=-4b+35 | | 8-5b=-4b+18 | | 2-7a=-a-70 | | 6w-3=-w+67 | | -5a+8=2a+50 | | -10+3w=-6w-100 | | 4w+10=-w+45 | | 7w+7=3w-25 | | -6n-10=-3n-28 | | -4n-2=-7n-35 | | 3+4a=6a+13 | | -w+8=-7w-58 | | (x-2)-4(x-3)=x+3-3(x-4) | | -k+1=k-23 | | 4k+10=-7k+10 | | -7d-9=-6d-9 | | 6n-3=4n+7 | | -4b-7=6b-77 | | 7k+1=56-4k | | x-10=-22+4x | | -1+2b=4b+23 | | 3t+6=6t+42 | | b+6=-6b+34 | | 6d+5=d-25 | | -5b+3=2b-11 | | 7x+10=4x+10 | | 3(w-3)+3/7=3 | | 5b+7=47+b |

Equations solver categories